Malawi, Social Accounting Matrix (SAM), 1998 - International Food Policy Research Institute (International Food Policy Research Institute, 2003)
The 1998 Malawi SAM includes 38 productive activities and three distribution activities (trade and transport margins). Of the 38 productive activities, the SAM includes 11 agricultural activities, 18 manufacturing activities and 9 service activities. The SAM also distinguishes between small-scale and large-scale activities in three of the agricultural sectors: tea, coffee, and other crops. There are 8 labor categories distinguished by type of occupation and level of education; two land factors (small-scale and large-scale); and three capital factors. Finally, the SAM distinguishes 14 household types, three enterprises accounts, two government accounts, an investment/saving account, and a rest-of-the-world account. For a description of the construction and use of this dataset, download the Trade and Macroeconomics Division Discussion Paper Number 69: (PDF 137K)